Penerapan Metode Pembelajaran Kooperatif Tipe Numbered Head Together Dalam meningkatkan Hasil Belajar IPAS - Nurhidayah Nur; Aldino (CV. Master Literasi Indonesia, 2026)
Meaningful learning is inherently supported by various contributing factors, one of which is the learning model. Based on observations conducted by the researcher from April 6th to 11th, 2026, in Grade III at SD Negeri 155/II Tagan Senamat Ulu, Bungo Regency, it was found that the actual learning process in Science and Social Sciences (IPAS) showed a low level of student mastery, specifically regarding the material